Pengaruh Iradiasi Sinar Gamma pada Karakter Kualitas Hasil Umbi Tiga Aksesi Ubi Kayu (Manihot esculenta Crantz) Asal Bangka: Pengaruh Iradiasi Sinar Gamma pada Karakter Kualitas Hasil Umbi Tiga Aksesi Ubi Kayu (Manihot esculenta Crantz) Asal Bangka - Iz Damaita; Tri Lestari; Rion Apriyadi (Universitas Bangka Belitung, 2018)
Cassava (Manihot esculenta Crantz) is a food crop plant carbohydrate after rice and corn. Bangka local cassava has different starch content at each accession. The purpose of this study was to know the effect of irradiation treatment on the quality of Bangka local cassava and national variety. This research had been conducted on October 2017 – January 2018, at experimental and research gardens, agrotechnology laboratory, and Science laboratory of the Faculty of Agriculture, Fishery and Biology, University of Bangka Belitung. This research used split-plot design with the main plot is irradiation treatment while the subplot is accession or variety of cassava. Data analyzed by using F test with 95% of significant levels. The observations results showed that irradiation treatment and accession varieties cassava affecting the tubers quality. Irradiation is the best treatment because this treatment has the best value on starch content, water content, and cyanide acid content. Type of accession affected the quality of the tubers. Rakit accession is the best accession which can make as flour because it has the best starch content, water content, flour rendemen, dan amylose content. There was an interaction between irradiation and accession on the value of ash content and cyanide acid content.